PENERAPAN ALGORITMA NEURAL NETWORK UNTUK KLASIFIKASI KANKER PARU - Evy Priyanti (Bianglala Informatika, 2021)
Neural Network Algorithm is an algorithm that is used to study the workings of the human brain which is applied to neurons connected to billions of network requirements and is able to work in many data learning processes, in this case the neural network algorithm will study the classification of lung cancer. Lung cancer is the third largest type of cancer in Indonesia. Lung cancer is divided into three classes of lung cancer pathologically. Class 1 consists of 9 observations, class 2 consists of 13 observations and class 3 consists of 10 observations. The results of lung cancer testing with this neural network algorithm produce an accuracy value of 75%, thus the neural network algorithm can be ascertained in classifying the pathology of lung cancer obtained from a survey by Stefan Aeberhard with a total sample size of 32 people and a total of 57 attributes. , one class label attribute and 56 attributes in the form of a nominal integer with a limit between 0-3 classes in the UCI Dataset.